The Role of Counselors in Improving the Psychological Well-Being of College Students - Azizah, Aulia Nur (PT. Anagata Sembagi Education, 2025)
Students' psychological well-being is an important aspect in supporting academic success and personal development. Counselors in universities play a strategic role in helping students overcome psychological challenges, such as stress, anxiety, and burnout, while building resilience, motivation to learn, and healthy social relationships. This study aims to examine the role of counselors in improving the psychological well-being of students and examine the implications of digital counseling services in the modern era. This article uses a narrative approach based on a literature review, highlighting different forms of counseling services, including individual counseling, group counseling, psychoeducation, career counseling, and crisis support. The results of the study showed that each counselor service had a significant positive impact, including improving emotion regulation, reducing stress, increasing academic motivation, and creating a more supportive social environment. In addition, digital service innovations, such as e-counseling and technology-based applications, have been proven to be able to expand access and increase the effectiveness of psychological support for students. The discussion emphasized that optimizing the role of counselors requires campus policy support, continuous training, and technology integration by paying attention to data security and privacy aspects. The conclusion of this study emphasizes the importance of strengthening digital-based counseling services to answer new challenges in supporting students' mental health in a sustainable manner